Molecular imaging in Libman-Sacks endocarditis. Issue 4 (April 2015) - Dahl, Anders; Schaadt, Bente K.; Santoni-Rugiu, Eric; Bruun, Niels E.
Abstract: We present a 54-year-old woman with systemic lupus erythematosus (SLE), fever, pericardial effusion and a mitral valve vegetation. 18 F-Fluorodesoxyglucose positron emission tomography CT ( 18 F-FDG-PET-CT) showed very high accumulation of the isotope at the mitral valve. The patient underwent cardiothoracic surgery and pathologic examinations showed characteristic morphology of Libman-Sacks vegetations. All microbiological examinations including blood cultures, microscopy, culture and 16s PCR of the valve were negative and the diagnosis of Libman-Sacks endocarditis was convincing. It is difficult to distinguish Libman-Sacks endocarditis from culture-negative infective endocarditis (IE). Molecular imaging techniques are being used increasingly in cases of suspected IE but no studies have previously reported the use in patients with Libman-Sacks endocarditis. In the present case, 18 F-FDG-PET-CT clearly demonstrated the increased glucose uptake caused by infiltrating white blood cells in the ongoing inflammatory process at the mitral valve. In conclusion, 18 F-FDG-PET-CT cannot be used to distinguish between IE and non-infective Libman-Sacks vegetations.